Web-Based Parent Training With Telephone Coaching Aimed at Treating Child Disruptive Behaviors in a Clinical Setting During the COVID-19 Pandemic: Single-Group Study With 2-Year Follow-Up - Saana Sourander; Minja Westerlund; Amit Baumel; Susanna Hinkka-Yli-Salomäki; Terja Ristkari; Marjo Kurki; Andre Sourander (JMIR Pediatrics and Parenting)
Abstract BackgroundThere is a lack of studies examining the long-term outcomes of web-based parent training programs implemented in clinical settings during the COVID-19 pandemic. ObjectiveThe aim is to study 2-year outcomes of families with 3‐ to 8-year-old children referred from family counseling centers to the Finnish Strongest Families Smart Website (SFSW), which provides digital parent training with telephone coaching aimed at treating child disruptive behaviors. MethodsCounseling centers in Helsinki identified fifty 3‐ to 8-year-old children with high levels of disruptive behavioral problems. Child psychopathology and functioning as well as parenting styles and parental mental health were collected from parents at baseline; posttreatment; and at 6-, 12-, and 24-month follow-ups. ResultsThe SFSW program had positive long-term changes in child psychopathology and parenting skills. Improvements in child psychopathology, including Strengths and Difficulties Questionnaire total score (Cohen dPdPdPdPdPdP ConclusionsThe study shows that the SFSW parent training program can yield significant long-term benefits. Findings indicate that the benefits of the treatment may vary between different parenting styles, which is important to consider when developing more personalized parenting interventions.